PASAR: SIMPUL PERSEBARAN BUDAYA DI KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Endy Marlina; Arya Roland; S Sudaryono; Atyanto Dharoko (Diponegoro University, 2013)
The study which aimed to uncover the values underlying the creation and development of the market in Bantul regency is base on the idea that space can be viewed as a space (physical form that can be seen visually) and as a place (the container of human activities that may reflect cultural values of the user them). This study was conducted with the paradigm of phenomenology and found that pekenan as a mobilization system of economic in the Javanese community in the district of Bantul, dominated by social values that develop a market as a socioeconomic space. Market as an economic activity container has a major role as a social networking nodes and important node in order to disseminate of culture in the district of Bantul. This study also found that the cultural values underlying the economic activity in the market is togetherness, partnership, civility, and harmony, they are local wisdoms of the people which are able to maintain the sustainability of the system of pekenan - mobilization system of the economic activity in the district of Bantul.